Emergency Support System: Actionable Real-time Intelligence with Fusion Capabilities and Cartographic Displays (Advances in Military Technology, 2022)
This paper describes the Emergency Support System (ESS), which is an FP7 European Project (funded from 2009 to 2013), as well as a suite of real-time (spatial) data-centric technologies, which will provide actionable information to crisis managers during abnormal events. The approach guiding the ESS project and architecture is based on the fusion of variable forms of field-derived data, including data obtained from unmanned aerial vehicles (UAV), unmanned ground stations (UGS), air balloons and cell-phone trackers (IMSI catcher), as well as on data obtained from external Web services (supplying mostly spatial data and functionality based on spatial data) and external crisis management systems (e.g. command and control systems). Fused data are visualized on the ESS portal.
Keywords: Data fusion; Sensor Web Enablement; Cell-phone detection; Cartographic visualization; Crisis management